Third-Person Perception as a Mediator of the Influence of Social Networking Sites Use and Personal Relevance to Preventive Behavioural Intention - Edwin, Joseph; Salamah, Ummi (UI Scholars Hub, 2021)
News coverage on Covid-19 is important as it provides people with important updates as well as crucial information for avoiding infection. Previous studies have shown undesirable messages such as Covid-19 news that circulates in social networking sites can trigger ‘third-person perception (TPP)’, which is a phenomenon in which audiences presume a message exerts more influence upon people other than themselves. It is crucial to examine whether audiences experience TPP during consumption of pandemic news – especially when there is a possible negative correlation between TPP and protective behavioural intentions. Previous studies showed empirical evidence when users used Covid-19 news in SNS (consume, contribute or create), such use could reduce TPP and was also correlated with preventive behavioural intentions. This suggests that three types of SNS usage and personal relevance have direct relationship with protective behavioural intentions, as well as indirect relationship with TPP, where it has a mediating role. To test these hypotheses, explanatory research of a positivistic paradigm and quantitative approach was administered. This research utilized quota sampling to collect data from 400 respondents through online questionnaire. Based on the structural analysis, there is no significant relationship between TPP and preventive behavioural intentions. Analyses also did not support the hypotheses that TPP mediated: 1.) SNS usage and preventive behavioural intensions; 2.) and personal relevance and preventive behavioural intensions. Personal relevance was found to be an important construct as it had a positive influence toward preventive behavioural intentions and a negative relationship with TPP. It is suggested that low level of interaction with Covid-19 news in Social Networking Sites is due to the respondents only incidentally consumed Covid-19 news. It is also suggested that non-existing relationship between third-person perception and preventive behavioural intention is due to the mandatory nature of health protocol in Indonesia.